Are We Obliged to Enhance for Moral Perfection?. Issue 5 (5th September 2018) - Archer, Alfred
Abstract: Suppose, we could take a pill that would turn us into morally better people. Would we have a duty to take such a pill? In recent years, a number of philosophers have discussed this issue. Most prominently, Ingmar Persson and Julian Savulescu have argued that we would have a duty to take such a pill. In this article, I wish to investigate the possible limits of a duty to take moral enhancement drugs through investigating the related question of whether it would be desirable to create a world populated entirely with morally perfect people. I argue, drawing on the work of Bernard Williams, Susan Wolf, and Michael Slote, that we have reason to be grateful that we do not live a world in which everyone is morally perfect, as this would prevent people from dedicating their lives to valuable nonmoral projects. I then argue that this thought should serve as a limitation on attempts to morally improve people through the use of technology. Finally, I explore the implications of this discussion for some of the less ambitious forms of moral enhancement currently being explored in the literature. I argue that these forms of enhancement give us no reason to worry about preventing valuable, morally imperfect ways of life. In fact, by acting as a shortcut to moral development, they might serve as an aid to help people fulfill valuable nonmoral goals in a way that is morally permissible.